Universal Basic Income in the Defense Economy during the Covid-19 Pandemic - Nadia Indah Rosalina; Guntur Eko Saputro; Luhut Simbolon (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The impact of the COVID-19 pandemic prompted the government to carry out social assistance programs. The purpose of this study is to analyze Universal Basic Income as a response to the COVID-19 pandemic which can simultaneously strengthen the defense economy in Indonesia as a form of peace dividend. This study uses a systematic literature study method of relevant previous research and strategy theory by identifying ends, ways, and means. The results of this study support universal basic income as a government policy (way) to deal with crises due to the COVID-19 pandemic because UBI can provide an increase in Indonesia's economic growth and empower Indonesian people to be better prepared to face risks, which will encourage people to dare to innovate. UBI can also strengthen the defense economy in Indonesia because by reducing the poverty rate, unemployment rate, and social inequality, the crime rate caused by the economy will decrease, increase in human resources, stronger community relations (ends). The means (means) needed to implement UBI in Indonesia are the budget, existing regulations, human resources (HR), and the latest data on Indonesian society.